Grass Phl p5 aeroallergen quantification in outdoor air samples: correlation with pollen counts - Antunes, Célia M. (2008)
Currently allergen exposure is estimated from pollen counts in air samples. However, there is not yet enough evidence to establish this technique as a reliable indicator of allergen exposure. Presently, there are a few reliable and sensitive ELISA methods that allow allergen quantification in environmental air samples but none is known to quantify Poaceae allergens. The aim of this work was to develop a novel approach to quantify Phl p5, one of the main allergen from Phleum pratense.